Role and application of study skills for tertiary-level english courses: teacher and student perspectives - C. Y., Dwee; M. Anthony, Elizabeth (Universiti Putra Malaysia Press, 2017)
Even though Malaysian students attend 11 years of formal English language classes in primary and secondary school and continue to learn English at tertiary level, for many undergraduates, using the English language competently is still a challenge. This may be attributed to the lack of study skills among students; using the right study skills is synonymous with autonomous learning. This paper draws on findings of a university research project and aims to report on an investigation into the role and application of study skills in tertiary-level English courses. Lecturers/teachers and students from a Malaysian university formed the study sample and the focus was on their perception. Purposive sampling was used to select the samples, while data collected via semi-structured interviews were analysed using a grounded theory approach. Classroom observations were also used to support the findings. The findings of this qualitative study revealed a mismatch between the perception of lecturers/teachers and students of study skills due to their differing expectations. Nevertheless, there was general agreement among the lecturers/teachers that should study skills be taught in tertiary-level English courses, it should be embedded within the course content and not exist as a separate, stand-alone entity. The study concludes with recommendations to direct future research.